Avaliação do uso de processos de separação por membranas na remoção de metais, recuperação de ácido sulfúrico e na geração de água de reúso a partir de efluente de indústria de mineração de ouro - Barbara Caroline Ricci (2015)
Several liquid effluents are generated during gold ore extraction and processing. Due to high concentrations of heavy metals and sulfuric acid, the effluent from pressure oxidation process is noteworthy. Given this scenario, this study aimed to investigate the performance of nanofiltration (NF) and reverse osmosis (RO) in the treatment of effluent from pressure oxidation process, aiming at recovery of metals and sulfuric acid and also water reclamation. In NF and RO tests, the commercial membranes MPF-34 and TFC-HR were employed respectively. Both membranes were supplied by Koch Membrane Systems. The study was divided into three parts. At first, NF potential in separation of sulfuric acid from nickel and cobalt sulfates was evaluated. RO potential in sulfuric acid concentration was also evaluated. Synthetic solutions were used in both assessments. For NF, high acid permeation (~ 100%) and high rejection of metals (>90%) were observed. For RO, a high rejection of sulfuric acid (>88%) was observed, when synthetic solutions with pH greater than 1 were evaluated. The results showed that RO and NF processes can be associated in the treatment acid solutions contaminated with metals. In the second part of this study, the NF and RO association in the treatment of real effluent from oxidation pressure process was evaluated. The proposed route allowed for: the recovery of a purified acid stream; the production of a metal enriched stream; the generation of high quality reuse water; a significant reduction in lime demand for neutralization in comparison to current demand. In the last part, the effect of continuous exposure to effluent in the NF and RO characteristics was investigated. In order to simulate the continuous exposure to the effluent, the membranes were immersed in real effluent and in synthetic acid solutions for eight weeks. For MPF-34, after eight weeks to exposure to real effluent, it was observed a decrease of 33% in cobalt and nickel rejections. That result indicated a reduction of NF ability in separation of metals from acid solution. Thus, the reduction of NF membrane selectivity would result in an acid production with a lower degree of purity. Also, a portion of the noble metals would be lost in NF permeate. Under these circumstances, a more stable membrane should be evaluated for industrial scale application of the proposed treatment route. Regarding to TFC-HR, the results indicated that the membrane showed a satisfactory stability under the acidic conditions employed in this investigation, thus exhibiting potential for application in real scale.